Gentrification in the wake of a hurricane: New Orleans after Katrina. (October 2019) - van Holm, Eric Joseph; Wyczalkowski, Christopher K
Hurricane Katrina struck the city of New Orleans in August of 2005, devastating the built environment and displacing nearly one-third of the city's residents. Despite the considerable literature that exists concerning Hurricane Katrina, the storm's long-term impact on neighbourhood change in New Orleans has not been fully addressed. In this article we analyse the potential for Hurricane Katrina to have contributed to patterns of gentrification during the city's recovery one decade after the storm. We study the association between Hurricane Katrina and neighbourhood change using data on the damage from the storm at the census tract level and Freeman's (2005) gentrification framework. We find that damage is positively associated with the likelihood of a neighbourhood gentrifying in New Orleans after one decade, which drives our recommendations for policy makers to take greater concern for their communities during the process of rebuilding from storm damage.